2012
DOI: 10.1007/s00216-012-6513-6
|View full text |Cite
|
Sign up to set email alerts
|

Rapid phytochemical analysis of birch (Betula) and poplar (Populus) foliage by near-infrared reflectance spectroscopy

Abstract: Poplar (Populus) and birch (Betula) species are widely distributed throughout the northern hemisphere, where they are foundation species in forest ecosystems and serve as important sources of pulpwood. The ecology of these species is strongly linked to their foliar chemistry, creating demand for a rapid, inexpensive method to analyze phytochemistry. Our study demonstrates the feasibility of using near-infrared reflectance spectroscopy (NIRS) as an inexpensive, high-throughput tool for determining primary (e.g.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 29 publications
4
41
0
Order By: Relevance
“…Specifically, the combination of individual compounds increases the probability that a detection threshold of concentration, and its subsequent effect on leaf spectra, will be surpassed (Rubert‐Nason et al . ). We found that the prediction of tremulacin in fresh leaves across 500 permutations of the data was more stable than that of salicortin.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Specifically, the combination of individual compounds increases the probability that a detection threshold of concentration, and its subsequent effect on leaf spectra, will be surpassed (Rubert‐Nason et al . ). We found that the prediction of tremulacin in fresh leaves across 500 permutations of the data was more stable than that of salicortin.…”
Section: Discussionmentioning
confidence: 97%
“…; Rubert‐Nason et al . ; Kokaly & Skidmore ). Moreover, coefficient weightings and VIP statistics from models predicting tannins and salicinoids were most pronounced in these literature‐reported regions, corroborating the conclusion that the bending and stretching of C–H and O–H bonds are important for spectroscopic prediction of plant phenolics (Shenk, Workman & Westerhaus ; Kokaly & Skidmore ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This species has high cold‐tolerance (Li et al , Puhakainen et al ) and is widely planted in north China. It is an economically important tree species and its wood is used primarily for lumber, pulpwood, fuelwood and plywood (Valanne , Lannenpaa et al , Pavlo et al , Reimann et al , Borrega et al , Huang et al , Rubert‐Nason et al ). It is worth emphasizing that birch wood is particularly suitable for making plywood.…”
Section: Introductionmentioning
confidence: 99%